Pengembangan LKPD Berbasis HOTS dan Inkuiri Terbimbing pada Mata Pelajaran Otomatisasi Tata Kelola Humas dan Keprotokolan Kelas XII OTKP Semester Gasal di SMKN 10 Surabaya - Adelia Septiarini; Durinta Puspasari (Universitas Negeri Surabaya, 2020)
Development student worksheet based on HOTS and guided inquiry was conducted to implementation scientific learning of the 2013 Curriculum revised efforts to integrated 21st Century Skill. In addition, the research development student worksheet is also useful as learning subject automation public relation and protocol for class XII student OTKP SMKN 10 Surabaya. The study aims is to describing the development process of student worksheet, analyze the worthiness of student worksheet, and analyze students responses to the developed student worksheet. The research used the development research with 4D development model by Thiagarajan (1974) covering four stages is define, design, develop, and disseminate. However, this research was only until develop stage. Because in this research just aims to develop product of student worksheet based HOTS and guided inquiry for subject automation public relation and protocol of class XII student OTKP SMKN 10 Surabaya. The subjects of the research is trial to 20 student of class twentieth OTKP 1 SMKN 10 Surabaya. The result show that the developed LKPD was very feasible to be use as teaching material in terms of validations result of material feasibility is 97,25%, language feasibility 81,42%, and feasibility of graphic 98,66%. If averaged, the result of product feasibility obtained a percentage of 92,43%. Then, the students response result obtained score of 98,50% with very interested category. Based on these result it can be concluded that the student worksheet based HOTS and guided inquiry in th subject of Autamation of Public Relations and Protocol Management was feasible to be used as teaching materials and supporting major teaching materials for student during the learning process.